Implementasi Model Pembelajaran Project Based Learning dalam Memfasilitasi Keterampilan Berpikir Kritis Siswa SD - Rahmawati, Galih; Atmojo, Idam Ragil Widianto (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the implementation of Project Based Learning (PjBL) learning in an effort to facilitate students' critical thinking skills at SD Negeri Brangkal 2 Gemolong. The PjBL model is a learning approach that focuses on completing real projects as a medium to encourage the formation of critical thinking skills, cooperation, and problem-solving skills. This study uses a qualitative approach with a case study design, involving students and teachers who play a role in the implementation of PjBL. Data collection was carried out through in-depth interviews, participatory observation, and document analysis related to the project-based learning process. The results of the study show that the application of PjBL is able to facilitate or strengthen students' critical thinking skills, characterized by an increase in the ability to analyze, evaluate, and formulate arguments logically. In addition, students become more active in discussions and group work, and show increased confidence in expressing opinions and ideas. However, in its implementation there are several obstacles, such as suboptimal time management and limited resources. This research contributes to the development of more effective learning methods to improve the quality of education in elementary schools, and can be used as a reference for other schools in implementing PjBL to develop students' critical thinking skills.